Osteoarthritis of the hip and osteoporosis of the proximal femur - Cooper, C; Cook, P L; Osmond, C; Fisher, L; Cawley, M I (Annals of the rheumatic diseases, 1991)
A negative association has been reported between osteoarthritis and osteoporosis. There are, however, few population based data to support this association. In this study the bone density in the upper femur was compared with the presence and severity of hip osteoarthritis in 314 subjects undergoing radiography for non-skeletal indications. There was a statistically significant negative association between the two disorders. This relation may reflect differences in the cause of these two major musculoskeletal conditions.